Female School Teachers’ Knowledge Regarding Cervical Cancer - Thapa, Usha; Paudel, Manish; Malla-Pradhan, Rajeshwori (Morgan Journal of Interdisciplinary Research Studies, 2024)
Cervical cancer is a globally leading cause of mortality and morbidity in females. It is a curable cancer if diagnosed in the early stage. Lack of awareness of screening methods, risk factors, and early symptoms may lead to a late diagnosis. This study aimed to assess the knowledge regarding cervical cancer among female school teachers. A cross-sectional study design was adopted to assess the knowledge regarding cervical cancer among 106 female teachers. A non-probability purposive sampling technique was used to select the sample. Data was collected using a structured self-administered questionnaire and subsequently entered into IBM SPSS version 22 for analysis. The findings of the study revealed that the mean age was 30.45±3.911 and the majority of respondents were married (95.3%). Similarly, 72.6% of respondents had bachelor-level education, and 12.3% respondents had a family history of cervical cancer. Regarding the level of knowledge, the majority (64.2%) had a good level of knowledge, 25.5% had moderate level of knowledge, and 10.4% had poor level of knowledge. There was a significant association between levels of knowledge and religion (p=0.006). Findings indicate that a substantial percentage of respondents possess a good level of knowledge on cervical cancer.